2017
DOI: 10.1371/journal.pone.0170356
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Anillin-eGFP Reporter Marks Late Dividing Retinal Precursors and Stem Cells Entering Neuronal Lineages

Abstract: Monitoring cycling behaviours of stem and somatic cells in the living animal is a powerful tool to better understand tissue development and homeostasis. The tg(anillin:anillin-eGFP) transgenic line carries the full-length zebrafish F-actin binding protein Anillin fused to eGFP from a bacterial artificial chromosome (BAC) containing Anillin cis-regulatory sequences. Here we report the suitability of the Anillin-eGFP reporter as a direct indicator of cycling cells in the late embryonic and post-embryonic retina.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the combination of transgenes, genetic mutants and in vivo time-lapse imaging to visualize dynamic processes under physiological conditions would almost certainly help understanding more about the pathophysiology of LESCs/Wif1/Wnt related diseases. For instance, inducible systems to transiently activate Wif1 in injured wild type or Wif1 mutant embryos, which carry additional transgenes like anillin and signaling reporter to simultaneously highlight cell proliferation (Paolini et al, 2015; Cepero Malo et al, 2017) and Wnt signaling activity (Moro et al, 2012) would be an excellent tool to study Wif1 dependent regeneration processes in vivo . The fact that cornea structure, development and maintenance appear comparable between zebrafish and mammals (Pan et al, 2013; Takamiya et al, 2015) should encourage to exploit the zebrafish as in vivo model to understand the role of Wif1 in corneal regeneration and homeostasis.…”
Section: Wif1 In Stem Cell Plasticity and As Therapeutic Target In Thmentioning
confidence: 99%
“…However, the combination of transgenes, genetic mutants and in vivo time-lapse imaging to visualize dynamic processes under physiological conditions would almost certainly help understanding more about the pathophysiology of LESCs/Wif1/Wnt related diseases. For instance, inducible systems to transiently activate Wif1 in injured wild type or Wif1 mutant embryos, which carry additional transgenes like anillin and signaling reporter to simultaneously highlight cell proliferation (Paolini et al, 2015; Cepero Malo et al, 2017) and Wnt signaling activity (Moro et al, 2012) would be an excellent tool to study Wif1 dependent regeneration processes in vivo . The fact that cornea structure, development and maintenance appear comparable between zebrafish and mammals (Pan et al, 2013; Takamiya et al, 2015) should encourage to exploit the zebrafish as in vivo model to understand the role of Wif1 in corneal regeneration and homeostasis.…”
Section: Wif1 In Stem Cell Plasticity and As Therapeutic Target In Thmentioning
confidence: 99%
“…For example, research with breast, ovarian, lung, bladder, and prostate cancer cell lines revealed that dormancy competent cells entered states of dormancy and survival in response to high matrix stiffness, whereas dormancy-incompetent cells rapidly died. Both proliferative and metabolic activity were inhibited, and chemoresistance was increased in these dormant cells ( 125 132 , 145 ). Ongoing research is developing ways to induce cancer cells to exit dormancy by using biomaterials.…”
Section: Implications For Disease Severity and Clinical Outcomementioning
confidence: 99%
“…Despite some differences in expression, distinct identification of RSCs versus RPCs has been challenging [ 43 ]. New markers or transgenic-labelling of CMZ populations have emerged, and recent molecular labelling has shown that RSCs are specifically labelled by rax/rx2 [ 44 ], whereas the F-actin binding protein, anillin , labels late RPC populations in fish species [ 45 ]. A third CMZ subregion contains committed RPCs that express multiple different proneural genes, and these cells will ultimately produce the post-mitotic cells present in the fourth and final zone found closest to the border with the central retina [ 6 , 11 ].…”
Section: Distinct Cell Types Within the Cmz Niche And Their Proliferative And Multilineage Potentialmentioning
confidence: 99%